THE INFLUENCE OF QUIZIZZ APPLICATION IN LEARNING EVALUATION TO IMPROVE COLLEGE STUDENTS’ LEARNING OUTCOMES - Dwi Cahaya Nurani; Fahmi Surya Adikara; Yanuar Akhmad; Mar'atul Faida (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The government’s policy to enforce online learning during the Covid-19 pandemic brings about a variety of new learning innovations. One of them is the innovation in the evaluation process. This research aimed to know the influence of Quizizz Application in learning evaluation for the learning outcomes of PGSD students in Learning Strategy courses. This research was quasi-experimental research. This research was conducted by categorizing the experimental group by using Quizizz Application and the control group by using googleform. In this research, the population was all students of Elementary School Teacher Education (PGSD) STKIP Muhammadiyah Batang (20 students). The samples were selected through cluster random sampling. The data were collected through tests and observations. Then, the data were analyzed by descriptive statistics and t-test. The result showed that t-result was -30.304 with the significance level of < 0.05, which was 0.000. It could be concluded that applying Quizizz in learning evaluation significantly influenced the students’ learning outcomes. Thus, Quizizz application can be used by teachers as a learning media to design attractive and innovative learning evaluations in online learning.